Navigating Challenges of SAFe Adoption in Horizontally Sliced Agile Teams - Jain, Rakhi; Butler, Jeffrey (Journal of Knowledge Management Practice, 2025)
The Scaled Agile Framework (SAFe) enables IT organizations to implement agile practices on a larger scale, extending beyond conventional team-level agility. IT organizations that adapt SAFe practices across multiple teams often encounter significant challenges in coordination and integration. Agile practices can be opted in SAFe using horizontal or vertical slicing strategies. However, the horizontal slicing can impede time to market and hinder the operations of cross-functional teams. In contrast, vertical slicing prompts alignment, synchronization, and integration in product development. This article navigates the challenges associated with adopting horizontal slicing in the SAFe model. The authors have presented the insights favoring vertical slicing as a more effective approach.
Keywords: knowledge management; Scaled Agile Framework (SAFe); horizontal slicing; vertical slicing; agile development; agile process improvement